The effects of rider specific Pilates on rider position from a lateral view: a six week study - Boden, E. R.; Brigden, C.; Randle, H. (World Congress of Performance Analysis of Sport IX, 2012)
The equine industry and rider community is increasingly acknowledging that rider strength and fitness is vital in achieving the best results in competition. Other sporting disciplines are more aware of the potential of the utilisation of additional methods to improve performance such as Pilates. For example Pilates is commonly used to develop optimal strength and balance in modern dance and ballet. In the absence of published work on the benefits of Pilates on rider posture, the aim of this study was to investigate if Pilates improves rider posture whilst mounted. Riders (n=10) undertook a British Dressage recognised, Pilates training regime for a total of 6 weeks. The measurements were taken on horseback before the Pilates training commenced, after the third session and a final filming session was carried out after the six weeks, in walk, rising trot, canter left and canter right. Each rider had 3D spherical markers attached at specific anatomical landmarks; top of hat, shoulder, hip and heel. Using Quintic Sports Biomechanics Video Analysis Software package a line was drawn through the hip marker and the deviation of each marker from this line was recorded. All data were normally distributed and Multivariate Analysis of Variance was used to determine the effects of individual (rider), time (week) and horse gait. Engagement in a Pilates training regime had a significant effect on rider position (from a lateral view) (F2,316=35.81; p<0.001). The mean deviation from the ear, shoulder, hip heel (ESHH) alignment prior to the Pilates was 50mm ± 70mm in comparison to the (30mm ± 41mm) after the 6 week course had been completed. Rider profiles and horse gait (F9,316=37.11; p<0.01 and F3,316=31.49; p<0.001 respectively) also had a significant influence on deviation from the ESHH alignment. Other factors such as rider profiles (F9,316=37.11; p<0.01) had a significant effect as well as the effect of gait on the deviation from the ESHH alignment. The largest variation in deviation was found between walk (29mm±47mm) and rising trot (55mm ± 60mm) which is in line with other literature findings on the impact of the rider whilst travelling in walk and rising trot. Even though the study was undertaken on a relatively small sample of British Dressage affiliated riders, this study suggested significant results that using Pilates as an additional exercise method over a six week period leads to a significant improvement in rider position.